PENDAMPINGAN PEMBUATAN PUPUK DAN PESTISIDA ORGANIK GUNA MENDUKUNG USAHA BUDIDAYA STROBERI PADA KELOMPOK TANI SIDA URIP DESA SERANG KEC. KARANGREJA PURBALINGGA - Herliana, Okti; Hadi, Sapto Nugroho; Cahyani, Wilis; Rostaman, Rostaman (Jurnal Abdi Insani, 2024)
Strawberries have various benefits for human health so they are widely loved by the public. Serang Village, Karangreja District, Purbalingga. This village is located on the slopes of Mount Slamet with an altitude of about 650 - 1,600 m dp is one of the centers of strawberry cultivation in Central Java, but since 2016 it has experienced a decline in production due to poor quality seeds, high fertilizer prices, declining soil fertility and the existence of pests and plant diseases. The purpose of this research-based community service activity is to implement the results of the research to solve the problems that exist in the Sida Urip farmer group, provide training in making organic fertilizers and pesticides, assist in the practice of making organic fertilizers and pesticides, improve skills in maintaining strawberry plants, so that it can increase strawberry production The method used in this activity is Rural Appraisal Participation, which is the active involvement of all elements of the target audience, the stages of the activity include: Survey, socialization of activities, training, practice, demonstration plot making and evaluation. The results of the activity showed that there was an increase in the knowledge and skills of farmer groups in making compost and biological agents to support environmentally friendly strawberry cultivation. The eco-friendly strawberry demonstration plot produces 38.69 kg/bed of strawberries and conventional strawberry cultivation land produces 37.45 kg/bed. The assistance carried out by the service team also increased enthusiasm and cohesiveness among members of the Sida Urip farmer group.